Culturally Competent Communication in Health Care: Why It Matters - Bakić Mirić, Nataša M.; Kulić, Danijela G.; Butt, Sophia (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Establishing a more inclusive and culturally literate health care system is critical to supporting health care as a basic human right regardless of the legal status of patients. To do this, health care providers must be culturally equipped to respond to patients who come from different cultural spaces and have different worldviews, attitudes, and beliefs towards the social practice, including the concept and treatment of illness. Studies in the field of health care have shown that medical professionals need additional training in culturally competent communication, especially in ethnically heterogeneous surroundings, where potential barriers such as different languages, cultural norms, history between groups, ethnocentrism, etc., might pose obstacles to effective interaction between health care practitioners and patients. This paper offers some solutions to the possible communication gaps and suggests skills and strategies that might be taught to medical students and staff through mandatory or elective courses which would include: remaining silent with the patient; remaining non-judgmental; showing acceptance of what the patient is saying; giving recognition; offering oneself; giving the patient the opening; leading the discussion; making observations; encouraging communication; and paraphrasing. Adequate cultural competence can ensure that patients receive the care they need to live healthier lives irrespective of race, ethnicity, gender or sexual orientation.
Keywords: culturally competent communication; health care; health care providers; patients